2018
DOI: 10.1038/s41598-018-30786-y
|View full text |Cite|
|
Sign up to set email alerts
|

Extracellular vesicles protect glucuronidase model enzymes during freeze-drying

Abstract: Extracellular vesicles (EVs) are natural nanoparticles that play important roles in intercellular communication and are increasingly studied for biosignalling, pathogenesis and therapy. Nevertheless, little is known about optimal conditions for their transfer and storage, and the potential impact on preserving EV-loaded cargoes. We present the first comprehensive stability assessment of different widely available types of EVs during various storage conditions including −80 °C, 4 °C, room temperature, and freez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 42 publications
3
63
1
Order By: Relevance
“…Interestingly, a major size drift was observed when storing these OMVs at 4 °C (Figure 2d). Until now, there are very little reports on a standardized and preferred method for storing OMVs and EVs yet although it is essential for advanced studies [42,47] and storage of vesicles at -80 °C is recommended [48]. Our results indicate that freeze-drying is a valid alternative for storing OMVs as it was also shown in literature [42,49].…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, a major size drift was observed when storing these OMVs at 4 °C (Figure 2d). Until now, there are very little reports on a standardized and preferred method for storing OMVs and EVs yet although it is essential for advanced studies [42,47] and storage of vesicles at -80 °C is recommended [48]. Our results indicate that freeze-drying is a valid alternative for storing OMVs as it was also shown in literature [42,49].…”
Section: Resultssupporting
confidence: 72%
“…Each OMV sample was stored in PBS and at 4 °C, -20 °C, -80 °C and freeze dried to evaluate their stability [42]. Aliquots of 100 µL of each sample were kept in MaxyClear microtubes (Axygen) to avoid vesicles absorption to the plastic surface of the tubes.…”
Section: Storage Stability Of Omvsmentioning
confidence: 99%
“…In this context, cryoprotectants such as trehalose, already used for labile proteins, vaccines, and liposomes, appear to have a positive impact on EVs . Additionally, Frank et al reported that freeze‐drying does not significantly impact the size and particle number of MSC‐derived EVs and that, upon addition of cryoprotecting sugars, the enzymes in the lyophilized EVs have comparable activity to the ones in EVs stored at −80 °C.…”
Section: Storage and Stabilitymentioning
confidence: 99%
“…In recent years, it has been observed that stability and final activity of freeze-dried materials critically depend on how the entire approach is performed. [22][23][24][25] Essentially, this is based on different freezing and drying stresses, such as solute concentration, formation of ice crystals, pH changes and others, that are prone to denature proteins in the material to various degrees. 22 Thus, stabilizers are often required in a protein formulation to protect its stability in the final processed material.…”
Section: Introductionmentioning
confidence: 99%